Beyond Words: A Literature Review on Pragmatics in Cross-Cultural Communication and Its Impact on Employee Performance - Ibnu Zaki, Haris; Basrowi; Khaeruman (Center of Language and Cultural Studies, 2024)
Effective cross-cultural communication is essential in today’s globalized workplace, where employees from diverse linguistic and cultural backgrounds interact daily. Pragmatics, which examines how meaning is conveyed beyond literal words, plays a crucial role in ensuring mutual understanding and minimizing misinterpretations. This literature review explores the intersection of pragmatics and cross-cultural communication, analyzing its impact on employee performance. Key aspects such as speech acts, implicate, politeness strategies, and context-dependent meaning are examined in relation to workplace dynamics. Findings suggest that pragmatic competence enhances collaboration, reduces conflicts, and fosters a more inclusive work environment, ultimately improving employee productivity and job satisfaction. However, challenges such as cultural biases, misaligned communication expectations, and power distance issues may hinder effective pragmatic adaptation. The review highlights the need for targeted training programs and organizational policies that promote pragmatic awareness to optimize intercultural workplace interactions. Future research should further investigate industry-specific applications and the role of technology in facilitating pragmatic competence across cultures.